1999
DOI: 10.1063/1.1149485
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic diagnostics of an atmospheric microwave plasma for monitoring metals pollution

Abstract: A 1.5 kW, 2.45 GHz microwave sustained plasma in a flowing sample of stack exhaust gas has been shown in recent DOE/EPA testing to be an accurate monitor of trace hazardous metals (in the part per billion range) such as lead, chromium, and beryllium. Optical-UV spectroscopic studies are being carried out to better understand this particular atmospheric pressure plasma torch. An experimental device has been modified with extra visible access for radial and axial profile measurements. Diffraction limited fiber o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…1-11 Such an interest stems from their potential and actual use in various applications, including excitation sources for elemental analysis, [12][13][14][15][16][17][18][19] lighting [20][21][22] and, more recently, purification of noble gases obtained from air distillation 23 and remediation of gas effluents detrimental to the environment. 24 -26 A.…”
Section: Introductionmentioning
confidence: 99%
“…1-11 Such an interest stems from their potential and actual use in various applications, including excitation sources for elemental analysis, [12][13][14][15][16][17][18][19] lighting [20][21][22] and, more recently, purification of noble gases obtained from air distillation 23 and remediation of gas effluents detrimental to the environment. 24 -26 A.…”
Section: Introductionmentioning
confidence: 99%
“…The work described in this paper is limited to measurements of Fe I excitation temperatures and NH rotational temperatures (along with overlapping spectral features of the nitrogen second positive band) as a function of axial location inside the microwave torch under identical plasma conditions. It is worth mentioning the work of Woskov et al 14 , who conducted similar spectroscopic diagnostics on an atmospheric microwave plasma. In that study, they extracted T rot from the N 2 + (0,0) first negative system and T exc for Fe I in nitrogen and air plasmas, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…In the case of MW plasma it has been shown that a resonant cavity is not necessary for sustaining the plasma [11,12]. Large volume microwave plasma was generated using a commercial microwave oven at 2.45 GHz [13].…”
Section: Introductionmentioning
confidence: 99%